The Impact of Fatigue on Learning Concentration Through Self-Esteem as a Mediating Variable: Path Analysis Among Indonesian University Students - Abid Raisardhi Abdullah; Salsabila Nasution; Nurfaidah Ardis (Educational Guidance and Counseling Development Journal, 2026)
The digital transformation of higher education has intensified academic demands, placing university students at heightened risk of chronic fatigue that disrupts cognitive functioning. Despite growing awareness of this issue, the mechanisms through which academic fatigue impairs learning concentration, particularly the mediating role of self-esteem, remain underexplored in the Indonesian higher education context. This study examined the direct and indirect effects of academic fatigue on learning concentration, with self-esteem as a mediating variable. A total of 1,172 active university students across Indonesia were recruited via simple random sampling. Data were collected using three validated instruments: the Academic Fatigue Scale, the Self-Esteem Scale, and the Learning Concentration Scale. Path analysis using the lavaan package in RStudio confirmed that fatigue exerts a significant negative direct effect on self-esteem (β = -0.456, p < 0.001) and learning concentration (β = -0.306, p < 0.001). Self-esteem partially mediated the fatigue–concentration relationship, with an indirect effect of -0.089 (95% CI [-0.117, -0.059]) and a total effect of -0.396. Power analysis validated the sample’s adequacy, yielding statistical power exceeding 0.99—well above the minimum required threshold of 176 respondents. These findings demonstrate that academic fatigue undermines cognitive functioning both directly and indirectly by eroding students’ self-perception through mechanisms of internal sabotage and imposter syndrome. Theoretically, the results support Cognitive Load Theory and the Anxiety-Buffering Hypothesis within the digital higher education context. Practically, universities are recommended to implement Student Assistance Program (SAP)-based interventions, encompassing regular fatigue screening, cognitive load management training, and Cognitive Behavioral Therapy (CBT), to reinforce students’ self-esteem as a cognitive buffer and break the chain of fatigue’s adverse effects on academic performance.